2019
DOI: 10.33495/ijbfs_v7i2.19.102
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and fatty acid profile of Allanblackia seed oil and African pear pulp oils

Abstract: Edible oils were extracted from the pulp of African pear (Dacryodes edulis) and the seed of tallow tree (Allanblackia floribunda), given a yield of 48.93 and 65.31%, respectively. The oil samples were analyzed for chemical composition, physical properties, and fatty acid profile. Total saturated fatty acids of 51.64 and 34.12% were obtained from Allanblackia seed oil and African pear pulp oil, respectively, while 48.36% and 65.88% were recorded values for Total unsaturated fatty acids from Allanblackia seed oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
1
1
Order By: Relevance
“…This is evidence that the oil could be used in the soap making industry (Enengedi et al, 2019). Iodine value was 68.5 mgI/100g oil, close to other results obtained on D. edulis (Akusu & Wordu, 2019;Enengdi et al, 2019). These authors show that Iodine value range at 50.25 -58.05.…”
Section: Chemical Parameterssupporting
confidence: 88%
See 2 more Smart Citations
“…This is evidence that the oil could be used in the soap making industry (Enengedi et al, 2019). Iodine value was 68.5 mgI/100g oil, close to other results obtained on D. edulis (Akusu & Wordu, 2019;Enengdi et al, 2019). These authors show that Iodine value range at 50.25 -58.05.…”
Section: Chemical Parameterssupporting
confidence: 88%
“…The fatty acids order (%P>%O>%L>%S>%Ln) corresponds to the profile described by several authors on safou oils (Silou et al, 2002;Ondo-Azi et al, 2014). In opposite to the other authors, Akusu & Wordu (2019) reported another fatty acid order never described in safou oil: %O>%L>%P>%S, obtained on one sample from Nigeria. It's different from four profiles described on fatty acids from safou oil from Gabon among 213 safou trees respectively (Ondo-Azi et al, 2014).…”
Section: Fatty Acid Compositioncontrasting
confidence: 77%
See 1 more Smart Citation